Initiatives in the Process of Learning for the Digital Native Generation in the Post-Pandemic Period - Guspriadi, Yan; Nirwana, Herman; Neviyarni, Neviyarni; Ardi, Zadrian (Universitas Negeri Padang, 2022)
Post-pandemic conditions or also called new normal or other names that lead to the same meaning, in this condition personally, in groups, and organizations, some are adapting life processes, restarting everything that has been stopped due to the Covid-19 pandemic, direct interaction is replaced by interaction via the internet network, using a supporting platform, direct classroom learning is replaced by learning with virtual classes, ordering food through various applications, up to strict restrictions on mobility, this process occurs over a long period of time, Habits and behavior carried out by the digital native generation, has an effect on personal development academically and morally, when personally a person does routine things continuously, or is met with the same conditions many times, then indirectly a steady flow will be formed, regardless of whether it is negative or positive normally. Initiative is needed to increase motivation and learning outcomes. Initiative, independence, and responsibility in students will enable them to recognize opportunities, overcome obstacles, anticipate difficulties, and act appropriately and consistently.